Kinetic and Kinematic Analysis of Various Drop Jump Performances in Army Reserve Officer Training Corps Cadets. Issue 3 (March 2022) - Merrigan, Justin J.; O'Toole, Kyle B.; Wutzke, Clinton J.; Jones, Margaret T.
Abstract : Abstract: Merrigan, JJ, O'Toole, KB, Wutzke, CJ, and Jones, MT. Kinetic and kinematic analysis of various drop jump performances in army reserve officer training corps cadets. J Strength Cond Res 36(3): 738–746, 2022—The purpose was to examine effects of sex, drop height, and external loads on drop jump mechanics in Reserve Officer Training Corps cadets and whether findings were associated with strength. Males ( n = 14) and females ( n = 12) completed maximal isokinetic concentric (slow-C and fast-C) and eccentric (slow-E and fast-E) knee extensions and flexions at 60°·s −1 and 180°·s −1 . After 72 hours, 3 drop jumps were performed under 3 conditions (i.e., 30 cm unloaded [30UL], 30 cm loaded 15 kg [30L], and 60 cm unloaded [60UL]). No sex × condition interactions existed for any metric ( p > 0.05). The 30L condition resulted in slower eccentric and concentric center of mass (COM) and angular velocities, reduced concentric vertical ground reaction forces (vGRF), and lower jump performances. Although 60UL resulted in greater eccentric COM and angular velocities, peak vGRF, impulse, and rate of force development ( p < 0.008), no differences existed in jump performances. Males had faster COM and angular concentric velocities and smaller knee valgus angles, but no different vGRF compared with females. The change in the peak hip angle, because of 60UL, was associated with knee extension eccentric and concentric strength, whereas changes in knee angles were associated with eccentric strength. Likewise, eccentric strength influenced the effects of 30L on landing vGRF more so than concentric strength. Initial strength training is recommended, specifically emphasizing eccentric actions, before performing loaded (15 kg) drop jumps to reduce the increase of landing forces. However, caution may be required when performing drops from 60 cm because of increased forces, although no decline in jump performances were noted.